2022
DOI: 10.48550/arxiv.2203.01007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of quantum noise on the training of quantum Generative Adversarial Networks

Abstract: Current noisy intermediate-scale quantum devices suffer from various sources of intrinsic quantum noise. Overcoming the effects of noise is a major challenge, for which different error mitigation and error correction techniques have been proposed. In this paper, we conduct a first study of the performance of quantum Generative Adversarial Networks (qGANs) in the presence of different types of quantum noise, focusing on a simplified use case in high-energy physics. In particular, we explore the effects of reado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…These observations suggest that the noise is assimilated during the training, underlining the importance of using actual quantum hardware. This supports the findings of Borras et al [50], which empirically found that quantum generative adversarial networks can be efficiently trained on quantum hardware if the readout noise is smaller than 0.1. Thus, QCBMs seem to be an appealing application for NISQ devices.…”
Section: Discussionsupporting
confidence: 90%
“…These observations suggest that the noise is assimilated during the training, underlining the importance of using actual quantum hardware. This supports the findings of Borras et al [50], which empirically found that quantum generative adversarial networks can be efficiently trained on quantum hardware if the readout noise is smaller than 0.1. Thus, QCBMs seem to be an appealing application for NISQ devices.…”
Section: Discussionsupporting
confidence: 90%
“…The recent emergence of quantum machine learning [11] has lead to the proposal of various hybrid architectures, including QGANs [12][13][14][15][16][17][18][19][20][21][22]. Compared to other probabilistic models, GANs are especially well suited for implementation on quantum devices because they do not require exhaustive sampling during training.…”
Section: Previous Work On Gans and Qgansmentioning
confidence: 99%
“…The recent emergence of quantum machine learning [11] has lead to the proposal of various hybrid architectures, including quantum generative adversarial networks (QGANs) [12][13][14][15][16][17][18][19][20][21]. Compared to other probabilistic models, GANs are especially well suited for implementation on quantum devices because they do not require exhaustive sampling during training.…”
Section: Previous Work On Gans and Qgansmentioning
confidence: 99%
“…As we will later see, their architectures cannot be ported directly to our binary data. Furthermore, in [13,[20][21][22] as well as to a lesser extent in [16], the authors use a classical discriminator. In [18], the authors focus on learning 1-qubit quantum states.…”
Section: Previous Work On Gans and Qgansmentioning
confidence: 99%
See 1 more Smart Citation